3D printable robust shape memory PET copolyesters with fire safety via π-stacking and synergistic crosslinking. Issue 28 (5th July 2019) - Chen, Lin; Zhao, Hai-Bo; Ni, Yan-Peng; Fu, Teng; Wu, Wan-Shou; Wang, Xiu-Li; Wang, Yu-Zhong
Abstract : Multifunctional 3D printable polymers with fire safety are achieved from general PET by the π–π stacking and the synergistic crosslinking between phenylacetylene and phenylimide groups. Abstract : The practical problems of insufficient mechanical strength, poor processability, tedious synthesis and flammability facing shape memory polymers have limited their further usage in industrial fields, especially in construction and aerospace. A novel and very simple method of ternary polymerization is presented here to prepare multi-functional copolyesters from general poly(ethylene terephthalate) (PET) through the new well-designed third monomer that features pendent phenylacetylene–phenylimide units. The π–π stacking between phenylacetylene groups as a reversible net-point not only endows the copolyesters with good shape memory and self-healability, but also reinforces the interchain interaction, leading to high tensile strength (79.6–89.6 MPa). Interestingly enough, the phenylacetylene can synergistically crosslink with the unsaturated CN group generated from the phenylimide during burning, resulting in excellent flame retardancy. Thermoplastic smart copolyesters can be designed into fire alarms and can also be used for 3D printing. The printed geometries exhibit good shape memory behaviors, which could be deformed into a small size to save space during transportation/storage and allow manufacturing freedom for space applications.